การควบคุมแบบเซมิแอคทีฟของแบริ่งที่มีตัวหน่วงของเหลวแม่เหล็กอยู่ภายในภายใต้แรงกระทำสองทิศทาง - ณกรณ์ แก้วปิ่นทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Fluid dampers used in mitigation of seismic response of bridges in recent years are of the conventional piston type with unidirectional damping forces. When installed at the column pier to mitigate bidirectional response, the installation can be a problem because of limited space around pier tops. In this study, a magnetorheological-damper-embedded bearing are developed to response in two horizontal directions. Dynamic properties of the bearing are investigated. The developed MR-damper-embedded bearing composes of a cylinder containing the MR fluid and enamelled copper coils. The bearing is operated with a current of 1 ampere and a voltage of 10 volt. The dynamic test is performed using sinusoidal excitations with frequencies ranging from 0.5 to 1.5 Hz. with 15 mm maximum displacement in each direction. The increase of the damping force with the current and velocity is observed and the mathematical model of the damper is proposed. The effectiveness of MR bearing under the viscous-plus-variable-friction algorithm is investigated and the results show that the actual damping force is close to the commanded force. A discrepancy is observed to be about 6-11% in the damping force.